LA DOBLE FAZ DE LAS IMPLICACIONES DEL INVESTIGADOR | The double face of the researcher’s implications (Trabalho & Educação, 2016)
The analysis of the doubts and blockages I would like to share through this article concerns the research done during my doctoral research. The purpose of that study was to explore the authority position in a particular group of workers: the teachers. That research is based on the epistemology of complexity and its theoretical references are the various currents of French clinical social psychology, particularly the Sociopsychoanalysis, founded by Gérard Mendel. It was that psychoanalyst and sociopsychoanalyst who taught me the practical work in the field, and my research intended to be a tribute to him. I have entrusted the direction of that study to a renowned psychoanalyst who had created methodological tools generally used in psychotherapy clinic and rarely applied to social facts. The bet then was to discover the relevance of these instruments to analyze a case belonging to the social clinic. The story of the case that I will present, whose epistemological and theoretical references are the same as those of my thesis, will be referred to my thoughts on the various implications involved along the process of that research. It will be then same pieces of the professional autobiography of a subject who tries to objectify itself to get a better understanding of itself.___El análisis de las dudas y bloqueos que quisiera compartir a través de este texto están referidos a la investigación realizada por mi en el marco de mi tesis de doctorado, siendo el objeto de la exploración la constitución de la posición de autoridad en un particular colectivo de trabajadores(as): el de los(las) docentes. Esa investigación se apoya en una epistemología de la complejidad y sus referentes teóricos con las diversas corrientes de la psicosociología clínica francesa, en particular el Sociopsicoanálisis fundado por Gérard Mendel. Es con este psicoanalista y sociopsicoanalista con quien me formé para intervenir en el terreno, y a quien mi tesis debía rendir homenaje. La dirección de esa investigación fue confiada a un psicoanalista reconocido de la Argentina, creador de herramientas metodológicas habitualmente utilizadas en la clínica terapéutica y raramente aplicadas a los hechos sociales. La apuesta consistió entonces en descubrir su pertinencia para el análisis de un caso cuyo objeto se inscribe en el campo de una clínica de lo social. El relato que presentaré, cuyas referencias epistemológicas y teóricas son las mismas que las de mi tesis, concierne mis reflexiones sobre las distintas implicaciones que se jugaron en mí a lo largo del proceso de la investigación. Fragmento entonces de la autobiografía profesional de un sujeto que intenta objetivarse para comprenderse mejor.